Autophagy related genes mediated mitophagy in yeast, mammals and higher plants: Autophagy related genes mediated mitophagy - Riaz, Muhammad; Sultana, Razia; Ahmad, Javed; Mehmood, Azhar; Sattar, Saira; Hammad Tanveer, Muhammad; Zulkiffal, Muhammad; Sarwar, Muhammad (Cellular and Molecular Biology, 2024)
Autophagy is classified into macro-autophagy and micro-autophagy. Two major types of autophagy in the complex eukaryotic organism are microautophagy and macroautophagy. During microautophagy, cytoplasmic components that need to be degraded are taken up by lysosomes in animals and by vacuole in yeast and plants via the invagination of tonoplast. While macroautophagy is initiated after the formation of a cup-shaped membrane structure, a phagophore develops at cargo that grows in size and is sealed by double-membrane vesicles to form autophagosome; a generalized mechanism for degradation of the organelle. Autophagic removal of damaged mitochondria is a conserved cellular process to maintain a healthy mitochondrion called Mitophagy. In plants and animals, mitophagy has crucial roles in stress responses, senescence, development, and programmed cell death. Mitophagy appears in mammals, fungi, and plants but many genes that controlled mitophagy are absent from plants. Numerous studies have been conducted by using ATG mutants for the identification of functional roles of Autophagy Related Genes (ATG) required during the autophagy process at various steps like; auto phagosome formation, ATG protein recruitment, etc. The role of more than 25 ATG genes in mitophagy has been discussed in this review paper. The main parameters, reviewed and summarized in this review paper, are the name of species, common name, function, domain, deletion, induction, and localization of these autophagy-related genes in the cell. This review will facilitate the students, researchers, and academics for their further research insights.